Intranasal Delivery of Galanin 2 and Neuropeptide Y1 Agonists Enhanced Spatial Memory Performance and Neuronal Precursor Cells Proliferation in the Dorsal Hippocampus in Rats - Borroto-Escuela, Dasiel O.; Fores, Ramón; Pita, Mariana; Barbancho, Miguel A.; Zamorano‐Gonzalez, Pablo; Casares, Natalia García; Fuxe, Kjell; Narváez, Manuel (Frontiers in Pharmacology, 2022)
A need for new therapeutic approaches are necessary for dementia conditions and memory deficits of different origins, such as Alzheimer's disease. There is complex pathophysiological mechanisms involved, affecting adult hippocampal neurogenesis, in which neuropeptides and its neurogenesis regulation seem to participate. Neuropeptide Y(NPY) Y1 receptor (Y1R) and galanin (GAL) receptor 2 (GALR2) interact in brain regions responsible for learning and memory processes, emphasizing the hippocampus. Moreover, a significant challenge for treatments involving peptide drugs is bypassing the blood-brain barrier. The current study assesses the sustained memory performance induced by GALR2 and NPYY1R agonists intranasal coadministration and their neurochemical hippocampal correlates. Memory retrieval was conducted in the object-in-place task together with in situ proximity ligation assay (PLA) to manifest the formation of GALR2/Y1R heteroreceptor complexes and their dynamics under the different treatments. We evaluated cell proliferation through a 5-Bromo-2'-deoxyuridine (BrdU) expression study within the dentate gyrus of the dorsal hippocampus. The GalR2 agonist M1145 was demonstrated to act with the Y1R agonist to improve memory retrieval at 24 hours in the object-in-place task. Our data show that the intranasal administration is a feasible technique for directly delivering Galanin or Neuropeptide Y compounds into CNS. Moreover, we observed the ability of the co-agonist treatment to enhance the cell proliferation in the DG of the dorsal hippocampus through 5- Bromo-2'-deoxyuridine (BrdU) expression analysis at 24 hours. The understanding of the cellular mechanisms was achieved by analyzing the GALR2/Y1R heteroreceptor complexes upon agonist coactivation of their two types of receptor protomers in Doublecortin-expressing neuroblasts. Our results may provide the basis for developing heterobivalent agonist pharmacophores, targeting GALR2-Y1R heterocomplexes. It involves especially the neuronal precursor cells of the dentate gyrus in the dorsal hippocampus for the novel treatment of neurodegenerative pathologies as in the Alzheimer's disease.